Implementation of Trainer Kits in Project-Based Learning to Improve Critical Thinking, Motivation, and Competency of Electrical Engineering Students - Subuh Isnur Haryudo; Ekohariadi Ekohariadi; Munoto Munoto; Tri Rijanto; Farid Baskoro (Graduate School of Universitas Negeri Malang, 2021)
Abstract: Innovation of Project-based learning (PjBL) in the 21st century continues to be developed to improve learning outcomes. The use of Trainer kits presents several challenges in achieving learning objectives, both in terms of design, planning, and implementation. The purpose of this study is to implement the Automation of Electrical Installation trainer kit in project-based learning to increase student motivation, critical thinking, and competence. The research method uses research and development (R and D) with 4 models (Define, Design, Develop, Disseminate). Data collection techniques used theory tests and performance tests (measure of maximum performance type, MMP) and questionnaires (measure of typical performance type, MTP). The research trial used 120 respondents of final-level electrical engineering students from 3 universities in Surabaya, Indonesia. The resulting test of statistical analysis Wilcoxon using SPSS-23 obtained Asymp. Sig. (2-tailed) is valuable 0.000, meaning that there is an increase in the quality of learning on critical thinking skills, motivation, and competence of Electrical Engineering students by implementing a trainer kit in project-based learning.Abstrak: Inovasi Pembelajaran Berbasis Proyek di abad 21 terus dikembangkan untuk meningkatkan hasil belajar. Penggunaan Trainer kit menghadirkan beberapa tantangan dalam mencapai tujuan pembelajaran, baik dari segi desain, perencanaan, maupun implementasi. Tujuan dari penelitian ini adalah untuk mengimplementasikan trainer kit Otomasi Instalasi Listrik dalam pembelajaran berbasis proyek untuk meningkatkan motivasi, berpikir kritis, dan kompetensi siswa. Metode penelitian menggunakan research and development (R and D) dengan 4 model (Define, Design, Develop, Disseminate). Teknik pengumpulan data menggunakan tes teori dan tes kinerja (ukuran tipe kinerja maksimum, MMP) dan kuesioner (ukuran tipe kinerja tipikal, MTP). Uji coba penelitian ini menggunakan 120 responden mahasiswa teknik elektro tingkat akhir dari tiga universitas di Surabaya, Indonesia. Hasil uji analisis statistik Wilcoxon menggunakan SPSS-23 diperoleh Asymp. Tanda tangan (2-tailed) bernilai 0,000, artinya terdapat peningkatan kualitas pembelajaran keterampilan berpikir kritis, motivasi, dan kompetensi mahasiswa Teknik Elektro dengan menerapkan trainer kit dalam pembelajaran berbasis proyek.